2013
DOI: 10.1186/1472-698x-13-10
|View full text |Cite
|
Sign up to set email alerts
|

Association of Khat and alcohol use with HIV infection and age at first sexual initiation among youths visiting HIV testing and counseling centers in Gamo-Gofa Zone, South West Ethiopia

Abstract: BackgroundHIV/AIDS is the major problem and an obstacle to both the health and development of people in Ethiopia today. It is also indicated that the use of substances have dramatically increased despite the serious concern about HIV infection.MethodsUnmatched case control study was conducted in South West Ethiopia using a sample of 105 cases and 305 controls. Multivariate logistic regression was used to assess the degree of association between dependent and independent variables.ResultHIV infection was positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
29
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 9 publications
4
29
1
Order By: Relevance
“…A high prevalence of HIV in khat users is well documented, and HIV patients on antiretroviral therapy also chew khat concomitantly. 5,15,18 Ethiopia is a malariaendemic country. Plasmodium vivax malaria is responsible for 40% of total malaria cases in Ethiopia, and the only remedies are chloroquine and primaquine, which are metabolized by CYP2D6.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A high prevalence of HIV in khat users is well documented, and HIV patients on antiretroviral therapy also chew khat concomitantly. 5,15,18 Ethiopia is a malariaendemic country. Plasmodium vivax malaria is responsible for 40% of total malaria cases in Ethiopia, and the only remedies are chloroquine and primaquine, which are metabolized by CYP2D6.…”
Section: Discussionmentioning
confidence: 99%
“…14 The increasing daily use of khat in East Africa and Arabia is a major concern for public health. 6,15 There is evidence that herbdrug interactions represent a potential risk to patients taking conventional medicines, resulting in serious clinical consequences. 16 Cytochrome P450 3A4 and CYP2D6 are the 2 most important liver enzymes, metabolizing approximately more than 75% of all medications, 17 including antiretroviral, antimalarial, and antituberculosis drugs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Its effects are increased self esteem, increased levels of energy, increased libido and excitement [9][10][11] . Different studies revealed that frequent khat chewing has been associated with risky sexual behavior, predisposition to HIV, unwanted pregnancy, reduced school performance, adverse pregnancy outcome, and cardiovascular disorders [12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization report has shown that khat use causes dependency [15][16][17][18][19], predisposes the individual to myocardial infarction [20], ischemic heart disease [21], psychosis [22,23], distress [24], premature ejaculation [25], unprotected sex [26], manic episodes [27,28], oesophageal cancer [29], low birth weight and lactation problems [30], structural and functional brain changes [31,32], and criminal activity [33].…”
mentioning
confidence: 99%